2006
DOI: 10.1002/jcb.21027
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid regulates the affinity of the murine phosphatidylinositol 4‐phosphate 5‐kinase‐Iβ for phosphatidylinositol‐4‐phosphate

Abstract: Type I phosphatidylinositol 4-phosphate 5-kinase (PI4P5K) catalyzes the phosphorylation of phosphatidylinositol 4 phosphate [PI(4)P] at carbon 5, producing phosphatidylinositol 4,5 bisphosphate [PI(4,5)P2]. Phosphatidic acid (PA) activates PI4P5K in vitro and plays a central role in the activation of PIP5K pathways in vivo. This report demonstrates that actin fiber formation in murine fibroblasts involves PA activation of PIP5Ks and defines biochemical interactions between PA and the PIP5Ks. Inhibition of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Hence, PAR1 regulation of PIP 2 levels (which would probably affect PLD, because PLD requires PIP 2 for activation) (Brown et al, 1993;Liscovitch et al, 1994) may play a critical role in feed-forward signal amplification. This is consistent with findings that both PIP 2 and PA (shown here to be crucial for stable platelet aggregation) can bind to and activate PI5K in vitro (Jarquin-Pardo et al, 2007). PAderived DAG formation may also play a role in feed-forward signal amplification through PKC (Henage et al, 2006), a cellular modulator of PLD activation, as well as CalDAG-GEF, an activator of Rap1 known to be highly expressed in platelets.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, PAR1 regulation of PIP 2 levels (which would probably affect PLD, because PLD requires PIP 2 for activation) (Brown et al, 1993;Liscovitch et al, 1994) may play a critical role in feed-forward signal amplification. This is consistent with findings that both PIP 2 and PA (shown here to be crucial for stable platelet aggregation) can bind to and activate PI5K in vitro (Jarquin-Pardo et al, 2007). PAderived DAG formation may also play a role in feed-forward signal amplification through PKC (Henage et al, 2006), a cellular modulator of PLD activation, as well as CalDAG-GEF, an activator of Rap1 known to be highly expressed in platelets.…”
Section: Discussionsupporting
confidence: 91%
“…Early investigations revealed that PtdOH stimulated PIP5K activity from bovine brain membranes (Moritz et al, 1992) and later investigations revealed that only the class I PIP5Ks are stimulated by PtdOH (Jenkins et al, 1994). In vivo regulation of PIP5K by PtdOH has been documented as a significant decrease in PIP 2 levels in lysosomal membranes following butanol treatment (Arneson et al, 1999) and a decrease in PIP5K-dependent actin stress fiber formation after PLD inhibition in murine fibroblasts (Jarquin-Pardo et al, 2007). Recent studies demonstrated reduced PIP5K activity after treatment with small-molecule PLD inhibitors (Roach et al, 2012), further underscoring the importance of PtdOH in PIP5K regulation.…”
Section: F Activating Invasion and Metastasismentioning
confidence: 98%
“…Furthermore, it has been proposed that PA can regulate the affinity of PIP5K for PtdIns(4)P (Jarquin-Pardo et al, 2007). PA is generated through the hydrolysis of phosphatidylcholine (PC) by phospholipase D (PLD) or through the phosphorylation of DAG by diacylglycerol kinase (DGK) .…”
Section: Regulation By Arfmentioning
confidence: 99%